The superiority of economics and the economics of externalism – a sketch. Issue 4 (December 2019) - Winzler, Tim
Argument: The article takes as its starting point the relationship of academic economists and the wider society. First, various bodies of literature that deal empirically with this matter are discussed: epistemologically, they range from a bold structuralism via a form of symbolic interactionism to a form of radical constructivism. A Bourdieusian approach is recommended to complement these perspectives with a comprehensive perspective that is sensible to the cultural differences between social groups. Starting from the established notions of field, capital and habitus, the article then attempts to go the initial steps towards formulating a theory of the specificity of academic economics, taking Germany as its example. For that it uses and compares in-depth interviews of recognized and non-recognized German economics students. It shows the thorough interweaving of specific normative and positive dispositions into a conviction of objectivity and disinterestedness. This exploratory empirical induction furthers follow-up questions, the empirical answering of which may help to gain a more complete understanding of the actions and thoughts of economists in their specific contexts.